Pengaruh Implementasi Kebijakan, Karakteristik Individu, Karakteristik Organisasi Terhadap Motivasi Kerja Dan Kinerja Sekretaris Desa Di Kabupaten Mojokerto - Didik Chusnul Yakin (DIA: Jurnal Administrasi Publik, 2013)
This study aims to verify and analyze the effect of policy implementation appointment of secretary of the village into the civil service, individual characteristics, organizational characteristics of work motivation and performance of the village secretary. This study is a quantitative research survey explanatory (Burhan Bungin, 2010: 35) which will prove a causal relationship between independent variables (independent variables) are variables of policy implementation, the variable characteristics of the individual and organizational characteristics of the variable with the dependent variable (dependent variable) the variable work motivation and variable performance of the village secretary. Around 153 respondets taken as randomly from secretary of the village. Data collected by using questionaire list and analyzed using SPSS version 17.0 and SEM programs â€“ LISREL 8.50. Based on the research objectives, results and discussion in the research, conclusions can be stated: The implementation of the policy, organizational characteristics have a positive relationship to the motivation to work, while the individual characteristics have a negative relationship to the motivation to work. Patterns of relationships and patterns are a significant influence on organizational characteristics variables, whereas the pattern of relationships and patterns do not significantly influence the implementation of policies contained in the variable and individual characteristics. Tenth, work motivation, implementation of the policy and individual characteristics have a positive relationship to performance sekdes, whereas organizational characteristics have a negative relationship to performance. Patterns of relationships and patterns are a significant influence on the individual characteristics variables, whereas the pattern of relationships and patterns that no significant effect found on the motivation variable, implementation of policies and organizational characteristics.Â  Keywords: Implementation,individual and organizational characteristics, work motivation